OPTIMALISASI OPERASI BINA KUSUMA DALAM USAHA MENANGGULANGI PREMANISME DI WILAYAH HUKUM POLRES TANAH DATAR - Ramadan, Ahmad (UNES Law Review, 2019)
Bina Kusuma's Operation is the Operation of the West Sumatra Regional Police Control in order to suppress disruption of community security. One of the disturbances of Khamtibmas that occurred in the jurisdiction of the Tanah Datar police station was the act of thuggery. The problems that are examined are the implementation and constraints and optimization of bina kusuma operations in order to combat thuggery in the jurisdiction of the Tanah Datar police station by Bhabinkamtibmas. this research is legal research with analytical descriptive specifications. The implementation of the Operation Bina Kusuma at the Tanah Datar Police Station put forward the efforts of guidance and prevention. At Operation Bina Kusuma the Tanah Datar police station held raids on thugs to locations prone to thuggery and criminal acts. The constraints faced are the weakness of the planning system in developing a thuggery prevention plan. Optimizing the prevention of thuggery through bina kusuma operations at the Polres Tanah Datar can be done by realizing coordination and synchronization between district governments to jointly integrate and synchronize each task and its responsibilities according to its authority.